2015
DOI: 10.1038/srep18305
|View full text |Cite
|
Sign up to set email alerts
|

Nature of low-frequency noise in homogeneous semiconductors

Abstract: This report deals with a 1/f noise in homogeneous classical semiconductor samples on the base of silicon. We perform detail calculations of resistance fluctuations of the silicon sample due to both a) the charge carrier number changes due to their capture–emission processes, and b) due to screening effect of those negative charged centers, and show that proportionality of noise level to square mobility appears as a presentation parameter, but not due to mobility fluctuations. The obtained calculation results e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 38 publications
(72 reference statements)
1
28
0
Order By: Relevance
“…2(a)). In the majority of semiconductor devices 1/f α -type fluctuations originate from a superposition of many charge carrier generation-recombination (g-r) processes in the capture centres with widely distributed relaxation times [15]. These centres are formed during device fabrication and also during ageing due to the device degradation.…”
Section: Noise Characteristics Of Unaged Ledmentioning
confidence: 99%
“…2(a)). In the majority of semiconductor devices 1/f α -type fluctuations originate from a superposition of many charge carrier generation-recombination (g-r) processes in the capture centres with widely distributed relaxation times [15]. These centres are formed during device fabrication and also during ageing due to the device degradation.…”
Section: Noise Characteristics Of Unaged Ledmentioning
confidence: 99%
“…[35], the minimum number of relaxators (defects) has been estimated with relaxation times distributed in a wide time range needed for the generation of noise with the 1/f spectrum. It has been shown that this requirement is fulfilled when the relaxation times are arbitrarily distributed one-by-one in every two-octave range.…”
Section: What Is the Cause That The 1/f Noise Level In Semiconductorsmentioning
confidence: 99%
“…1, a (11) in Ref. [35] must be changed to the factor 0.16. The curve g(τ) for K = 1 has only small waves or bumps compared with g 0 (f).…”
Section: What Is the Cause That The 1/f Noise Level In Semiconductorsmentioning
confidence: 99%
See 2 more Smart Citations